(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2012)
The systems of leaked (filtered) adaptative consist principally of a sign of reference. From these two series of time, the system of leaked adaptative conditions his internal variables to obtain the wished response. In the specific case of a system of leaked adaptative for cancellation, there is needed the estimation of mathematical function that shapes the distortion that wants to avoid of the sign of entry. This article centres on the problem of removal of the displacement of the base line of the electrocardiogram (ECG) for which a system has been designed for the estimation of the sign of reference, by means of the method of polynominal regression, whisch takes different points of the electrocardiogram. The sign of estimated reference is applied to a system of leaked adaptative by cancellation for the base line of the ECCG.